Epika „epigramatyczna”. Ekkeharta Versus ad Picturas wobec tradycji poetyckiej - Smolak, Kurt (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2016)
As a consequence of the large variety of poetic genres dealing with biblical material in Christian-Latin literature of Late Antiquity, in the 11th century the two extremely opposite forms of poetic expression were artificially combined, namely continuous epic narration and epigrammatic conciseness of the so called tituli, that is to say metrical inscriptions which were meant to explain wall paintings or mosaics of selected biblical topics. By order of Aribo, archbishop of Mainz, Ekkehart IV of St. Gall composed an “epigrammatic epic”, which was to cover the wide range of the entire Bible from Genesis to Apocalypse, contemporary exegesis partly included. Aribo was supposed to select those “epigrammes” from this “biblical epic” which he needed for a new decoration of the cathedral – a project, however, which was never realised. Ekkehart’s highly manneristic poetic creation, preserved only in his autograph, MS 393 of St. Gall, remained unparalleled. Nevertheless, it is an important testimony of the experimental and innovative character of medieval Latin poetry in the period of transition from monastic literary production of the previous centuries to the golden age of medieval Latin classics, which originated in the cathedral schools, during the late 11th and the 12th centuries.